Eco energy, Energy aware and Net-zero Supply Chain - Sharifi Nevisi, Mohammad Mehdi; Salehi, Reza (International journal of industrial engineering and operational research, 2023)
The ever-increasing threat of climate change has prompted the need for developing sustainable solutions to meet energy demands. In recent years, eco energy, energy-awareness, and net-zero supply chain strategies have gained significant attention due to their potential in reducing greenhouse gas emissions and promoting environmental conservation. This paper aims to provide a comprehensive analysis of the current state of research and advancements in eco energy, energy awareness, and net-zero supply chain practices. It begins with an introduction to the concept of eco energy and its significance in mitigating climate change. Subsequently, it presents a survey of related work, identifying various strategies and technologies employed in energy awareness and net-zero supply chain frameworks. Furthermore, the paper presents key findings and results from case studies and real-world implementations. Ultimately, the research concludes by discussing the potential of eco energy, energy awareness, and net-zero supply chains in achieving sustainability goals and emphasizing the need for continued research in these areas